Significance Increased of Xanthine Oxidase Activity in Placenta with Pregnancy Complications of Preeclampsia and Gestational Diabetes Compared to Normal - Novientri, Gissi; Prijanti, Ani Retno (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2022)
Certain risky complications in pregnancy are due to failure of pseudo-vasculogenesis of arteria spiralis, which leads to inadequate nutrition, hypoxia, and inflammation. These can be caused by eating disorders, stress, or other risk factors. Preeclampsia (PE) and Gestational Diabetes (GD) are pregnancy complications that are currently of concern. In Indonesia, the prevalence of PE reaches 3-10%, with a maternal mortality rate of 50%. Meanwhile, the prevalence of GD ranges from 1.9-3.6%, and half of GD patients are diagnosed with type 2 Diabetes Mellitus (DM) after 5-10 years of giving birth. Oxidative stress arises as a result of those pregnancy complications. Various studies have also been conducted to determine the pathways that produce reactive oxygen species (ROS), the leading causes of oxidative stress. Xanthine oxidase (XO) is an enzyme that contributes to ROS production. Uniquely this enzyme is the converted form of xanthine dehydrogenase (XDH), which plays a minimal role in ROS production. The conversion of XDH to XO significantly increased in PE and GD cases, characterized by increased XO activity in maternal and fetal circulation and placental tissue compared to normal pregnancies. This paper will describe the conversion mechanism of XDH to XO in PE and GD conditions and compare its enzyme activity to normal pregnancy.